COLLEGE STUDENT´S COMMITMENT - Josefa Melgar Bayardo; Marie Leiner De La Cabada; Patricia Jimenez Terrazas (European Scientific Journal, ESJ, 2014)
Obtain commitment to college students who successfully complete a career is essential for developing countries, precisely considering we live in a dynamic and competitive world. Although several studies have been conducted as a variable taking student engagement in the literature search for the construction of the theoretical framework few studies have found that studied the relationship between commitment and the time students spend studying. The present study aims to identify whether the level of commitment to working students is different from those who dedicated exclusively to study. Variables have also been considered as the number of hours the student spends at work, reason for selection of the career, his current work relationship with his course, among others.